Hepatorenal protective efficacy of flavonoids from Ocimum basilicum extract in diabetic albino rats: A focus on hypoglycemic, antioxidant, anti-inflammatory and anti-apoptotic activities - Mohamed S. Othman (Elsevier, 2021)
Plant derived phytochemical therapy is a bright candidate for treatment of diabetes and its associated complications. Ocimum baslicum is used as an anti-diabetic traditional medicine. Hence, the present study investigated the effect of Hail Ocimum extract (HOE) and its total flavonoids (HOETF) against hepatorenal damage in experimental diabetes induced by high-fat diet (HFD) and injection of streptozotocin (STZ) in rats. Diabetic animals were co-treated daily with HOE, HOETF or metformin (MET) as a standard anti-diabetic drug for four weeks. Compared to controls, HFD/STZ-treatment lead to significant increases in fasting blood glucose, insulin and HOMA-IR levels. Furthermore, diabetic rats had elevated hepatic (ALT and ALP) and kidney functions (urea and creatinine) biomarkers together with disturbed lipid profile and decreased PPAR-γ gene expression. Higher levels of hepatic and renal LPO and NO paralleled with lower levels of GSH and activities of antioxidant enzymes (SOD, CAT, GPx and GR) after HFD/STZ treatment. Additionally, noteworthy inflammatory and apoptotic responses were evident in both organs of diabetic rats as witnessed by augmented levels of TNF-α, IL-1b and Bax levels with declined levels of Bcl-2. Moreover, histological examination of hepatic, renal and pancreatic tissues validated the biochemical findings. On contrary, co-treatment of diabetic animals with HOE or HOETF could decrease glucose and insulin levels together with improvement of lipid markers and alleviation of hepatorenal dysfunction, oxidative injury, inflammatory and apoptotic events. Conclusively, HOE or HOETF could be a promising complementary therapeutic option for the management of diabetic hepatorenal complication owing to their antioxidant, anti-inflammatory; anti-apoptotic properties.